Comparative Structural Properties of Nanosized ZnO/Fe3O4 Composites Prepared by Sonochemical and Sol-Gel Methods. Issue 1 (May 2019) - Nurul Ulya, Habibatun; Taufiq, Ahmad; Sunaryono
Abstract: In this research, the synthesis of ZnO/Fe3 O4 nanocomposites was conducted using sonochemical and sol-gel methods as well as natural materials as the primary raw material. The results of X-ray diffraction data analysis showed that the synthesis of nanocomposite used sonochemistry method which resulted in the sample with ZnO and Fe3 O4 phases without the presence of the others. Interestingly, the sol-gel method resulted in a sample with ZnFe2 O4 and α-Fe2 O3 phases without the presence of ZnO. This case happened since Zn formed oxide compound in the form of spinel zinc ferrite. By using the Scherrer equation, the crystallite sizes were of about 7.5 nm for Fe3 O4, 25.5 nm for ZnO, 13.6 nm for α-Fe2 O3, and 11.6 nm for ZnFe2 O4. The elemental compositions of the sample as the synthesis using sonochemical method were 33.08% for Fe and 66.91% for Zn. Meanwhile, the elemental compositions of the sample as the result of synthesis using the sol-gel method were 58.25% or Fe and 41.75% for Zn. Moreover, the infra-red spectrum showed that the functional group of the Fe3 O4 phase was observed on the wavenumber of 550 cm − 1 and 676 cm − 1; the functional group of ZnO phase was found on the wavenumber of 433 cm − 1; the functional group of α-Fe2 O3 was detected on the wavenumber of 479 cm − 1 and 551 cm − 1; and the functional group of ZnFe2 O4 was recorded on the wavenumber of 526 cm − 1. Thereby, the sonochemical method in this study provides a new alternative in the synthesis of ZnO/Fe3 O4 nanocomposite using natural material as the primary raw material.